Low-cost transition metal-nitrogen-carbon electrocatalysts for the oxygen reduction reaction: operating conditions from aqueous electrolytes to fuel cells - Cui, Li-Ting; Wang, Yu-Cheng; Zhou, Zhi-You; Lin, Wen-Feng; Sun, Shi-Gang (Sustainable energy & fuels, 2024)
After decades of effort, the performance of low-cost transition metal-nitrogen-carbon (M-N-C) catalysts has been significantly improved, positioning them as promising catalysts for the oxygen reduction reaction in proton-exchange-membrane fuel cells (PEMFCs). Despite this progress, compared to traditional commercial Pt/C catalysts, the practical application of M-N-C catalysts in PEMFCs is hindered by their inferior performance in acidic environments. In this perspective, we first summarize the current status of M-N-C catalysts in terms of activity and stability, and compare their performance with that of Pt/C catalysts. Then we discuss the fundamental research challenges associated with M-N-C catalysts, which are primarily related to (i) conducting basic research with tests exclusively using oversimplified aqueous electrolytes that limits exploration in practical fuel cell environments; (ii) lacking operando characterization methods under fuel cell working conditions; and (iii) the complexity of catalyst structures and fuel cell operating environments causing difficulty in M-N-C catalyst research. Lastly, we propose key advances that need to be made in the future to address these fundamental challenges, including the rational design of fit-for-purpose catalysts based on more cost-effective and efficient modelling, preparing model/quasi-model catalysts with defined and controllable structures, and developing operando characterization techniques for PEMFCs. By combined study using model/quasi-model catalysts, operando characterization methods and atomistic modeling, we can deeply understand the "structure-performance" relationship of the catalysts at various scales and develop next generation M-N-C catalysts that can meet the increased demand for PEMFCs. The rational design of M-N-C oxygen reduction catalysts for fuel cells.